Attention Focus and New Opportunities: The Moderating Role of Managerial Attention to Alternative Issues - Eklund, John; Raj, Manav; Eggers, J. P. (Organization Science, 2025)
The strategy literature highlights the critical role that managerial attention plays in shaping firms’ responses to industry change. However, attention to change alone is not sufficient to precipitate action. The context in which this attention is paid is also critical in determining the translation of attention to action as managers generally pay attention to multiple issues within their strategic agendas. We argue that attention to a competing issue and the breadth of managerial strategic attention impair the relationship between attention to a focal issue and related organizational action as these attentional constraints may lead to hesitancy or confusion at an individual level and reduced coordination at an organizational level. Realizing that at an organizational level, firms vary tremendously with respect to their sizes, resources, and by implication their overall attentional capacities, we argue that the negative moderation impacts of attention to a competing issue and the breadth of strategic attention on the attention to a focal issue–subsequent action relationship are larger for smaller firms. Studying the U.S. electric utility industry and the emerging new distributed electricity generation business model, we find broad support for our arguments and also important nuance. By melding theory, important details of our empirical setting, and intriguing empirical results, we develop greater insights into when and how the other strategic issues to which managers pay attention can shape the translation of managerial attention to a new business model into subsequent organizational action. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2021.15861 .